Optimizing the Needle - Thread - Fabric Interaction for Enhanced Seam Performance in Clothing Manufacturing - Le, Song Thanh Quynh; Nguyen Thi, Thuy My (EAI Endorsed Transactions on Sustainable Manufacturing and Renewable Energy, 2025)
In apparel industry, product quality is always the key factor determining the success of a business. Not only does this create customer satisfaction, but product quality also directly affects the business's reputation, competitiveness, and market expansion opportunities. In this, seam appearance is one of the most important quality requirements, directly determining customer satisfaction. This paper examines the relationship and impact of three most important specifications, including needle-thread compatibility, fabric weight on the quality of seam performance. Through the experiment according to the full factorial design, this paper has determined the influence of each factor, in which the fabric weight is the factor with the most significant impact on the variation of the seam length, followed by the needle size and thread size. Determining the relationship between material parameters (fabric, thread) and equipment parameters (needle) not only helps to minimize errors but also creates the premise for building standardization processes for technical parameters according to each specific product group. These results will support the operator to adjust the machine faster, more accurately and less dependent on manual experience, thereby improving productivity and efficiency of the whole system.
Keywords: clothing industry; seam performance; quality control; design of experiment